Accuracy of neuropsychological tests and the Neuropsychiatric Inventory in differential diagnosis between Frontotemporal dementia and Alzheimer's disease - Bahia,Valéria Santoro (2009)
Abstract The differential diagnosis between frontotemporal dementia (FTD) and Alzheimer's disease (AD) is sometimes difficult. Objectives: To verify the accuracy of neuropsychological tests and a behavioral disorders scale in the differential diagnosis between FTLD and AD. Methods: Retrospective data on 12 FTD patients and 12 probable AD patients were analyzed. The scores on neuropsychological tests (MMSE score, reverse digit span, delayed recall for drawings, semantic fluency of animals) and the Neuropsychiatric Inventory (NPI) in both groups were compared. Results: Both groups had similar performance on neuropsychological tests. All FTD patients and 50% of AD patients had neuropsychiatric abnormalities. The NPI score was 58.0±19.3 for the FTD patients, and 3.6±4.7 for the AD patients (p<0.01). Using a NPI cut-off score of 13, the sensitivity and specificity were 100% in this sample. The four most common neuropsychiatric disturbances in FTD patients were: apathy, aberrant motor behavior, disinhibition and eating abnormalities. Apathy and dysphoria/depression were the most common behavioral symptoms among the AD patients. Conclusions: In this study, NPI was found to be a useful tool for the differential diagnosis between FTD and AD. The neuropsychological tests commonly used in the medical office were unable to distinguish between the two groups.